Ambulatory monitoring of cumulative free-living activity. - Moy, M.L.
Discusses potential clinical applications of monitoring patients with chronic obstructive pulmonary disease (COPD). It is concluded that the ability to measure cumulative free-living activity in patients with COPD appears to have enormous potential clinical applicability. Ongoing research to develop unobtrusive, wearable sensors that extend monitoring periods and couple these data with wireless technology is needed. Research studies are also needed to assess the role measurement of cumulative free-living activity plays in both the clinical care of patients with COPD and clinical trials involving COPD, therapeutics. It may prove to be optimally used alone or in conjunction with existing measures of clinical status.
Keywords: Chronic obstructive pulmonary disease patients; Clinical care; Clinical status measures; Clinical trials; Cumulative free-living activity measurement; Monitoring periods extension; Unobtrusive wearable sensors; Wireless technology